PENGARUH FAKTOR TECHNOLOGY ACCEPTANCE MODEL TERHADAP PENERIMAAN PEMUSTAKA PERPUSTAKAAN DIGITAL SIMADU MACA - Ega Selly Anjani; Encang Saepudin; Andri Yanto (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2025)
This study examines the influence of the Technology Acceptance Model (TAM) factors on library users' acceptance. The TAM concept used in this research is based on the theory proposed by Davis (1989) and later modified by Al-Gahtani (2001). In this study, the TAM factor variable (X) is divided into two sub-variables: usefulness (X1) and ease of use (X2). The aim of this study is to determine whether the TAM factors influence the acceptance of the Simadu Maca digital library users. The research employs a quantitative method with multiple regression analysis, which attempts to assess the influence of two or more independent variables on a dependent variable. This study was conducted with 75 Simadu Maca digital library users who voluntarily registered through a link in the bio of the Subang Regency Public Library's Instagram account, selected based on simple random sampling techniques. The results show that all TAM factor sub-variables, namely usefulness (X1) and ease of use (X2), have a significant partial and simultaneous influence on the acceptance variable (Y), although the level of influence is weak. This study proves that the Simadu Maca digital library is beneficial and easy to use. However, when looking at its influence on user acceptance, some improvements are still needed in terms of the registration process, access from various devices, and the quantity and variety of collection. This means that good usefulness and ease of information technology do not fully guarantee digital library user acceptance.